2019
DOI: 10.1111/febs.15068
|View full text |Cite
|
Sign up to set email alerts
|

New homologues of Brassicaceae water‐soluble chlorophyll proteins shed light on chlorophyll binding, spectral tuning, and molecular evolution

Abstract: Type‐II water‐soluble chlorophyll (Chl) proteins (WSCPs) of Brassicaceae are promising models for understanding how protein sequence and structure affect Chl binding and spectral tuning in photosynthetic Chl–protein complexes. However, to date, their use has been limited by the small number of known WSCPs, which also limited understanding their physiological roles. To overcome these limitations, we performed a phylogenetic analysis to compile a more comprehensive and complete set of natural type‐II WSCP homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Note that, the implicit contribution V impl MN in eqn (10) corresponds to the vacuum coupling V 0,m MN in eqn (56), since the transition dipoles in the present model are non-polarizable. This screening factor (eqn (56)) is in agreement with earlier work by Hsu et al, 100 who, in addition, investigated the screening factors of higher order multipoles. They found that the screening factor increases with the order of the multipole, reaching 2/(e + 1) in infinite order.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Note that, the implicit contribution V impl MN in eqn (10) corresponds to the vacuum coupling V 0,m MN in eqn (56), since the transition dipoles in the present model are non-polarizable. This screening factor (eqn (56)) is in agreement with earlier work by Hsu et al, 100 who, in addition, investigated the screening factors of higher order multipoles. They found that the screening factor increases with the order of the multipole, reaching 2/(e + 1) in infinite order.…”
Section: Discussionmentioning
confidence: 92%
“…47 Due to its relatively simple structure, WSCP has been an important model system for the study of fundamental pigment-pigment and pigment-protein interactions. [48][49][50][51][52][53][54][55][56][57][58][59] Because of the approximate D 2 symmetry (Fig. 1), all four Chl a pigments have an equal average local excitation energy (site energy), and the excitonic coupling determines the splitting between exciton states that is seen in the spectra.…”
Section: Introductionmentioning
confidence: 99%
“…An important advantage of using type II WSCPs for studying spectral tuning is the ability to rigorously modify the protein environment of the Chls by assembling them in vitro with recombinantly expressed proteins [21][22][23][24] . By implementing this strategy, Bednarczyk et al 19 demonstrated a spectral tuning mechanism based on a single-point mutation accounting for two-thirds of the spectral shifts between CaWSCP, and LvWSCP.…”
mentioning
confidence: 99%
“…Class IIa WSCPs are characterized by a high Chl a/b binding ratio (>6), and have their bound Chl a lowest‐energy Qy absorption band at 673 nm. Class IIb WSCPs have a lower Chl a/b binding ratio (<3.5), and their Chl a Qy peak is at 663 nm (1,13). Recent crystallographic and spectroscopic work focusing on WSCPs from cauliflower ( Brassica oleracea ) (CaWSCP) (14), and Virginia pepperweed ( Lepidium virginicum) (LvWSCP) (15) as representatives of class IIa, and IIb WSCPs, respectively have laid out the molecular determinants of Chl Qy absorption band shifts as well as the factors affecting Chl a/b binding affinity (8,16).…”
Section: Introductionmentioning
confidence: 99%